The aspects of tumor prophylaxis in the course of the human papilloma virus infection - Bulsa, Marek; Czaja-Bulsa, Grażyna (Przewodnik Lekarza/Guide for GPs, 2011)
Infections with a human papilloma virus pose a new challenge in the struggle with neoplastic diseases. The work presents issues related to the prevention of chosen tumors. Also, potentially high effectiveness of vaccinations has been confirmed and the importance of health education and social awareness concerning neoplastic diseases have been pointed out.